Characterization and correction of fading effects in GeDOFs microdosimeter for absorbed dose measurements - Noramaliza Mohd Noor,; Nizam Tamchek,; Ung, Ngie Min; Mohd Taufik Dolah,; Muhammad Safwan, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study investigates the thermoluminescence (TL) fading of fabricated germanium-doped optical fibers (GeDOFs) with a focus on TL signal intensity, glow curve, best-fit curve, and correction factor. Two distinct GeDOFs geometries, cylindrical fiber (CF) and flat fiber (FF), were compared for TL intensity decay under 6 MV and 10 MV photon beams. TL intensity measurements were recorded from the first day post-irradiation to the 106th day and a comparison of two fading curve-fitting approaches was carried out. Fading correction factor (Kfad) was derived, and the corresponding uncertainties were calculated. Over time, GeDOFs exhibited a decline in TL intensity, with a notably rapid decay occurring in the initial 30 days after irradiation. The most substantial TL intensity loss was observed in FF, with values of 58.9% for 6 MV and 63.4% for 10 MV. The evaluation of curve fitting showed that the best conformity was achieved through a single exponential decay equation model. The area under the glow curve decreased as the time between GeDOFs irradiation and TL readout increased. Kfad was determined by comparing the fading function of reference GeDOFs to that of the measured ones. The estimated uncertainties associated with Kfad were found to be 0.06% for CF and 0.12% for FF, respectively. GeDOFs exhibit fading characteristics influenced by TL readout interval time and radiation energy. When quantifying the absorbed dose from photon beams, it is crucial to account for the fading correction factor to ensure the precise and accurate measurement of the dose.